Care in the prescription of Methylphenidate (Ritalin) in children with attention deficit hyperactivity disorder: a bibliographic review (Research, Society and Development, 2022)
Medications are important health tools, but their use should be carried out with care, evaluating the benefit/risk ratio and efficacy for clinical indication for which they are intended. With the objective of describing care in the prescription of Methylphenidate (Ritalin®) in children with attention deficit hyperactivity disorder, the study in question seeks to highlight the efficacy of Methylphenidate (Ritalin®) treatment of HRT and also to present the potential risks of misuse of the drug. The article was prepared through a bibliographic review in the Scientific Electronic Libraries Online (sciELO), Journal of Research Associations and Development, PUBMED and LILACS (Latin American and Caribbean Health Sciences Literature) collections, in which 30 articles were used for their development, and which was divided into four parts, introduction, methodology, pharmacological data and finally the results and conclusions obtained through the research.